Mapping of Global Research on Electronic Cigarettes: A Bibliometric Analysis - Li, Xuechao; Zhang, Ting; Zhao, Liang; Liu, Qiling; Shi, Chuandao; Zhang, Rongqiang (Frontiers in Public Health, 2022)
Electronic cigarettes (E-cigarettes) use has increased rapidly in the past decades and has been widely studied by scholars worldwide, whereas the research topics and development trends in this field are still unclear. This study aimed to explore the landscape of research relating to e-cigarettes. The data outputted from the Web of Science Core Collection database was used for bibliometric analysis. Frequencies and percentages were used to describe the publications' characteristics. Visualizing maps were designed using VOSviewer 1.6.9 and CiteSpace 5.8 R2. Overall, a total of 7,979 records were identified in the database and the number of researches increased rapidly since 2010. All publications involved 19837 authors, with the top ten authors contributing to 8.71% (695) of all documents. The most productive country and institution were the United States of America and the University of California San Francisco, respectively. Nicotine & Tobacco Research was not only the journal with the most published papers but also the most co-cited journal. The main research domains in this field were the prevalence, awareness, reasons for using e-cigarettes; e-cigarettes use for tobacco harm reduction; exposure in the population; and the relationship between e-cigarettes and tobacco and nicotine. E-cigarettes researches have become a popular field for scholars. The hot topics on e-cigarette research were extensive and changed over the past decade.